Physical Characteristics of Liposomal Formulation Dispersed in HPMC Matrix and Freeze-Dried Using Maltodextrin and Mannitol as Lyoprotectant - Raditya Weka Nugraheni (Tabriz University of Medical Sciences, 2017)
Background: The present study aims to design formulation of liposomes that are well-preserved during freeze-drying. The combination of Hydroxy Propyl Methyl Cellulose (HPMC) as dispersion matrix and lyoprotectants; maltodextrin or mannitol, was employed to prevent aggregation and/or recrystallization. The obtained dry products were investigated in terms of their physical characteristics. Methods: Liposomes were prepared using thin film method and hydrated with the lyoprotectant solution. The formed liposomes were mixed with HPMC gel and freeze-dried. The obtained solid products were characterized using Differential Scanning Calorimetry (DSC), X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). Results: The DSC thermograms of formulations with maltodextrin were relatively homogenous, yet exhibiting meta-stable properties. In contrast, the formulations using mannitol showed phase separation. These results were confirmed by XRD data, in which formulations with maltodextrin showed no intensive peaks, indicating amorphous solid while the formulations with mannitol exhibited more intensive peaks, indicating the presence of crystalline solids. The SEM images of both maltodextrin and mannitol-containing formulations showed porous matrix with spherical liposomes trapped in the matrices. The SEM images also correspond to the DSC and XRD data, where crystalline solid existed in the mannitol-containing formula. Conclusion: The developed liposomes formulation using combination of HPMC matrix and maltodextrin showed potential in preserving liposomes structure, contrary to those of using mannitol.